A Comparison of Executive Functions in Normal Aging, Mild_x000D_ Cognitive Impairmant, and Early Stage Alzheimer_x000D_ Type Dementia in Turkish Sample - (:unkn) unknown (My University, 2019)
Introduction: In this study, neuropsychological profiles of Mild Cognitive Impairment (MCI) and early-stage Alzheimer's Disease (AD) were explored with a comprehensive neuropsychological battery that evaluates attention, memory, executive functions, language, visual-spatial, and behavioral skills.Methods: In this study, 60 people with minimum primary school degree were included. Twenty people of those with early-stage AD (12 women, 8 men), while 20 people were with MCI (10 women, 10 men). These groups were matched for age, sex and education with 20 normal elderly subjects (9 emale, 11 male).Results: Our findings showed that the general cognitive profile of MCI is manifested as episodic memory and a semantic memory disorder. In contrast, in early-stage AD patients, language, visual-spatial skills, executive function, abstraction and interference resistance skills were found to be impaired and episodic and semantic memory problems were observed.Discussion and Conclusion: The results of the present study suggesting a distinguished profile of MCI can be a promising factor in distinguishing the fine boundary between MCI and early-stage AD with an opportunity for early diagnosis and treatment of AD in the Turkish sample.